BO`LAJAK O`QITUVCHILARNI KASBIY IJTIMOIYLASHTIRISHNING METODOLOGIK MASALALARI - Zohidova, S.R. (SCIENCE and SOCIETY, 2017)
The article deals with the methodological and theoretical issues of professional socialization of future teachers, socialization, the main criteria of socialization, criteria for determining methodological ideas, professional socialization, organizational and methodological criteria for professional socialization.
Keywords: professional socialization; criteria; historical criteria; logical criteria; dialectical criteria